(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
A growing number of public personalities, politicians, non-profit organizations, and members of civil society are demonstrating their social duty and dedication by adopting a green philosophy that focuses on three key areas: the environment, human well-being, and the green economy. The terms "green management", "green public procurement", "green marketing", "green human resource management" and "green PR" are becoming more and more popular to improve the environmental condition. Because of their mutual dependence, applying one idea promotes the growth and advancement of another. This study attempts to present a research model, on the one hand, emphasizing the thesis that environmental management should be viewed as a moral concern rather than an adaptable procedure and that it can influence as a source of competitive advantage by providing strategic and economic advantages [1]. The idea that the application of green practices in human resource management extends beyond the implementation of environmental protection initiatives and includes the formulation of policies and practices that support sustainable development and people management is another popular hypothesis in the field. Taking into consideration the interaction between institutions and human resources, the concepts of meaning, value, and integrative communication are strengthened in this context to create ideal conditions for the implementation of "green ideas" with a sustainable outcome. The conceptual linking of these management fields is presented in a 'management waterfall for re-innovation' model for positive, integrative 'green' organizational behavior. The aim of the study is to make a comparative analysis of the challenges facing the green management of human resources, summarizing and presenting some interesting ideas in this scientific field. Through comparative analysis, key characteristics are summarized and conclusions are drawn for the improvement of these processes. A series of empirical and theoretical analyses, a deductive technique, and a descriptive-correlative approach are all combined in the structure of scientific research. The research directs the rethinking of hierarchical structures in "networked" models based on cooperation between two functional areas of the organization and gives arguments supporting the idea.